2006
DOI: 10.1159/000090942
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin Levels and Haemoglobin Decline in Early Virological Responders and Non-Responders to Hepatitis C Virus Combination Therapy

Abstract: Therapeutic drug monitoring of ribavirin has been claimed to predict virological response and/or haematological side effects in patients with chronic hepatitis C undergoing peginterferon/ribavirin combination treatment. In the present study, steady-state ribavirin levels were retrospectively analyzed in serum samples from patients at week 12 of combination therapy with peginterferon alpha-2a or alpha-2b and ribavirin. Patients were classified as early virological responders on the basis of undetectable HCV-RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…High Rbv concentrations were associated with the occurrence of anemia but did not correlate with viral responses, in either the univariate or the multivariate analysis. Rbv dose and exposure have been associated with SVR for genotypes 1 and 4, 10 , 23 , 24 but this relationship has not been unanimously confirmed, with several studies suggesting that lower Rbv doses may be equally effective 25 , 26 , 27 , 28 . Although Rbv is indispensable in the current treatment for HCV, neither the susceptibilities of the different HCV genotypes to Rbv nor the relationship between plasma and intracellular (the true effect compartment) concentrations of Rbv are known.…”
Section: Discussionmentioning
confidence: 99%
“…High Rbv concentrations were associated with the occurrence of anemia but did not correlate with viral responses, in either the univariate or the multivariate analysis. Rbv dose and exposure have been associated with SVR for genotypes 1 and 4, 10 , 23 , 24 but this relationship has not been unanimously confirmed, with several studies suggesting that lower Rbv doses may be equally effective 25 , 26 , 27 , 28 . Although Rbv is indispensable in the current treatment for HCV, neither the susceptibilities of the different HCV genotypes to Rbv nor the relationship between plasma and intracellular (the true effect compartment) concentrations of Rbv are known.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to SVR, the relationship between ribavirin concentration and EVR remains controversial. In HCV‐mono‐infected patients, no significant correlation was found between serum ribavirin trough concentration and EVR at week 4 [17] or week 12 [18], while ribavirin plasma exposure after the first dose was significantly linked to the rapid virological response (RVR), and to a lesser extent, the EVR [15].…”
Section: Why Is Ribavirin a Good Candidate For Therapeutic Drug Monitmentioning
confidence: 99%
“…In a retrospective study, Donnerer et al found no correlation between ribavirin levels at week 12 and EVR [43]. By contrast, recent findings in HCV-HIV-coinfected patients suggested that a high ribavirin concentration could improve the EVR rate [44].…”
Section: "Several Analytical Methods Have Been Developedmentioning
confidence: 93%